2007
DOI: 10.1242/dev.001818
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of Mpl receptor during the establishment of definitive hematopoiesis

Abstract: *Cytokine signaling pathways are important in promoting hematopoietic stem cell (HSC) self-renewal, proliferation and differentiation. Mpl receptor and its ligand, TPO, have been shown to play an essential role in the early steps of adult hematopoiesis. We previously demonstrated that the cytoplasmic domain of Mpl promotes hematopoietic commitment of embryonic stem cells in vitro, and postulated that Mpl could be important in the establishment of definitive hematopoiesis. To answer this question, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 49 publications
(38 reference statements)
1
53
0
1
Order By: Relevance
“…But so far, very few extrinsic factors have been shown to be involved in the emergence, proliferation and survival of AGM HSCs. Mpl mRNA (which codes for the Tpo receptor) is found in the AGM hematopoietic clusters as tested by in situ hybridization (Petit-Cocault et al, 2007). Interestingly, AGM HSCs from Mpl -/-embryos have normal long-term repopulating potential but show a defect in the self renewal capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But so far, very few extrinsic factors have been shown to be involved in the emergence, proliferation and survival of AGM HSCs. Mpl mRNA (which codes for the Tpo receptor) is found in the AGM hematopoietic clusters as tested by in situ hybridization (Petit-Cocault et al, 2007). Interestingly, AGM HSCs from Mpl -/-embryos have normal long-term repopulating potential but show a defect in the self renewal capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to negatively modulate the development of hematopoiesis by stimulating the differentiation of PCLP + CD45 -cells to endothelial cells in the AGM region. Recently, the Thrombopoietin/Mpl signaling pathway has been shown to play a role in the regulation of HSCs in the mouse embryo (Petit-Cocault et al, 2007). Nevertheless, so far very few studies have clearly demonstrated an in vivo role of adult cytokines in embryonic HSC regulation.…”
Section: Growth Factors and Embryonic Hscsmentioning
confidence: 99%
“…5,15 However, Mpl mRNA expression can be detected in the AGM, fetal liver and yolk sac as early as E10.5, 34 …”
Section: Stem Cell Role For Tpomentioning
confidence: 99%
“…51,52 Subsequent studies of this model have demonstrated the role of TPO-MPL signalling in the regulation of HSCs in adult mice 53 and in the establishment of definitive hematopoiesis during embryonic development. 54,55 On the other hand, the presence of residual functional platelets in MPL-deficient animals point to the existence of other factors involved in platelet formation, and these mice have proved an extremely useful model to identify such factors. Various studies have shown that the interleukins IL-3, IL-5, IL-6, IL-11 and IL-17 do not participate in the residual thrombopoiesis.…”
Section: Congenital Amegakaryocytic Thrombocytopenia (Camt)mentioning
confidence: 99%